The undervalued self: social class and self-evaluation - Kraus, Michael W.; Park, Jun W. (Frontiers in Psychology, 2014)
Social class ranks people on the social ladder of society, and in this research we examine how perceptions of economic standing shape the way that individuals evaluate the self. Given that reminders of one’s own subordinate status in society are an indicator of how society values the self in comparison to others, we predicted that chronic lower perceptions of economic standing rank vis-à-vis others would explain associations between objective social class and negative self-evaluation, whereas situation-specific reminders of low economic standing would elicit negative self-evaluations, particularly in those from lower-class backgrounds. In Study 1, perceptions of social class rank accounted for the positive relationship between objective material resource measures of social class and self-esteem. In Study 2, lower-class individuals who received a low (versus equal) share of economic resources in an economic game scenario reported more negative self-conscious emotions relative to upper-class individuals. Discussion focused on the implications of this research for understanding class-based cultural models of the self, and for how social class shapes self-evaluations chronically.